EMOTIONS OF JEANNETTE WALLS: SEMIOTIC ANALYSIS OF THE FIRST CHAPTER FROM THE GLASS CASTLE - Habibi, Nabilah Ummih; Musdalifah, Musdalifah; Hasbi, Muh. (Journal of English Literature and Linguistic Studies, 2024)
This study uses a semiotic approach to analyze the emotions experienced by Jeannette Walls in the first chapter of her memoir entitled The Glass Castle. By focusing on the signs contained in the narrative, this research aims to reveal the complexity of feelings Walls experienced in dealing with her mother's condition. Based on the analysis of several fragments of the story, emotions such as surprise, fear, anger, sadness, disgust/disgust, and attraction were found, but no happiness. This absence of happiness shows that in difficult and stressful situations, negative emotions tend to dominate. This research demonstrates the power of memoirs in describing a person's emotional state and how these emotions can be understood through the signs present in the text. Using a semiotic approach, this research provides a deeper insight into the life experiences depicted in memoirs and confirms the importance of signs in understanding the emotional dynamics of characters.